The Impact of the Hai Yang Shi You 981 Event on Vietnam's Stock Markets. (December 2018) - Le, Thai-Ha; Park, Donghyun; Tran, Cong-Phu-Khanh; Tran-Nam, Binh
This study examines the extent to which the Hai Yang Shi You 981 (HD-981) event, the sudden deployment of a Chinese oil rig in disputed territorial waters near Paracel Islands in May 2014, affected the stock market performance of 20 sectors of the Vietnamese economy. The impact was measured in terms of stock returns, using daily data on stock market indices. The results strongly indicate that the HD-981 event significantly and negatively affected the overall performance of Vietnam's stock markets. There is, however, considerable variation across sectors. While most sectors which are heavily dependent on the economy of China were adversely affected, the impact on some sectors was negligible. By conducting this study on Vietnam's stock markets, we hope to generate implications and lessons for other emerging markets in the region. JEL Classification: G1, G14, C58